$latex 5s^{2} 5p^{3} (^{4}S)nl $ Levels of Xe III - Gallardo, Mario (1979)
Analysis of recent observations of the Xe III spectrum has yielded revised and extended identifications for the $latex 5s^{2} 5p^{3} (^{4}S)nl 6s, 7s, 6p, 5d, 6d $ and $latex 4f $ levels. Four of the previously known twenty-two levels have been rejected whereas sixteen new levels have been added. The ionization energy has been determined from isoelectronic comparisons. The value arrived at, 250 400 ±; 300 cm $latex^{-1} $, is some 9000 cm $latex ^{-1} $ lower than the presently accepted value.